Wound Treatment with Absorbent Dressing Technique for Post-operative Submandibular Abscess Patients - Suhanda Suhanda; Rita Ayu Andira; Gumelar Zati Rahayu (Inspirasi Foundation, 2023)
Objective: To present care for wound care interventions with absorbent dressing techniques as an effort to prevent signs of infection and complications in postoperative submandibular abscess patients. Methods: The method used is descriptive with a case study approach using nursing care that refers to the IDHS and SIKI books. The subject of this study was 1 patient with a nursing diagnosis of skin integrity damage in postoperative submandibular abscess patients who were treated in the Orchid Room of Banjar City Hospital. With data collection techniques include interviews, observation, physical examination and study documentation Results: From nursing care in postoperative submandibular abscess patients, the symptoms that emerged during the assessment were an open wound on the lower right cheek. The nursing problem that arises is damage to skin integrity related to surgical wounds which refers to the IDHS book. Interventions carried out to prevent signs of infection and complications are wound care with absorbent dressing techniques. During the intervention process, the action went smoothly until the evaluation. There is a change in the surgical wound improving, does not cause signs of infection and complications. So that the intervention has a positive impact on wound healing and has improved Conclusion: After the intervention of wound care with absorbent dressing technique, the surgical wound improved, did not cause signs of infection and complications, while the subjective data from the anamnesis, the client said the surgical wound had improved from the previous day.